Impact of the COVID-19 pandemic on the symptomatic diagnosis of cancer: the view from primary care - Jones, Daniel; Neal, Richard D; Duffy, Sean R G; Scott, Suzanne E; Whitaker, Katriina L; Brain, Kate (The lancet oncology, 2020)
The entire landscape of cancer management in primary care, from case identification to the management of people living with and beyond cancer, is evolving rapidly in the face of the coronavirus disease 2019 (COVID-19) pandemic.1 In a climate of fear and mandated avoidance of all but essential clinical services, delays in patient, population, and health-care system responses to suspected cancer symptoms seem inevitable. Patients might be reluctant to present because of fear of interacting with others, limited capacity to use video or teleconsultations, and concerns about wasting the doctor's time.6,7 For family doctors, the COVID-19 pandemic is affecting all aspects of normal working life, including a reduced workforce due to illness and self-isolation, and the reduced availability of appointments and investigations in primary and secondary care. The National Health Service guidelines state that patients will want to discuss whether the benefits of continuing active cancer treatment outweigh the risks of potentially being seriously unwell if they contract COVID-19, which is a role that could well fall to primary care.9 The UK cancer charity Macmillan Cancer Support reports that a quarter of calls to its support line are from patients with cancer who are anxious about COVID-19.10 Although cancer charities provide a vital support role, primary care needs to support the physical and mental health of patients for whom potentially lifesaving cancer treatments are being postponed.